1995
DOI: 10.1111/j.1440-1681.1995.tb01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Can We Recommend Fish Oil for Hypertension?

Abstract: 1. The ability of the n-3 fatty acids in fish oil to lower blood pressure has been established. Dietary fish oil supplementation is effective in mild hypertension and, in certain cases, as an adjunct therapy in drug-treated hypertension. Efficacy may be enhanced by restricting sodium intake. 2. The overall benefit of fish oil in hypertension, however, has not yet been fully evaluated. We still need further information on the relative efficacy of individual omega-3 fatty acids and on additional cardiovascular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Fish oils have been shown to depress the synthesis of both VLDL and triglyceride in the liver (Connor & Connor, 1990). It is debatable whether the n-3 fatty acids can lower blood pressure among normotensives but several studies have shown a signi®cant reduction among hypertensives (Morris et al, 1993;Appel et al, 1993;Pietinen, 1994;Howe, 1995;Rustan et al, 1997). The absence of signi®cant associations between diet and LDL, waist ± hip ratio and body mass index is in accordance with most studies.…”
Section: Discussionsupporting
confidence: 55%
“…Fish oils have been shown to depress the synthesis of both VLDL and triglyceride in the liver (Connor & Connor, 1990). It is debatable whether the n-3 fatty acids can lower blood pressure among normotensives but several studies have shown a signi®cant reduction among hypertensives (Morris et al, 1993;Appel et al, 1993;Pietinen, 1994;Howe, 1995;Rustan et al, 1997). The absence of signi®cant associations between diet and LDL, waist ± hip ratio and body mass index is in accordance with most studies.…”
Section: Discussionsupporting
confidence: 55%
“…The effect is greater with higher baseline pressure and in subjects with clinical atherosclerotic disease or hypercholesterolaemia. It can be enhanced by a concomitant restriction of the sodium intake (Morris et al, 1994;Howe, 1995). The potential blood pressure lowering mechanism is discussed by Das (Das, 2004).…”
Section: Hypertensionmentioning
confidence: 99%
“…In contrast to the difficulty in establishing clinical antihypertensive benefits of dietary Ω‐6 fatty acid supplementation, evidence that increased consumption of the long‐chain Ω‐3 fatty acids in fish and fish oil can lower blood pressure is growing rapidly 30 . The most‐likely mechanism is a shift in eicosanoid production away from the 2‐series prostaglandins derived from arachidonic acid to the 3‐series prostaglandins derived from eicosapentaenoic acid (EPA), the 20‐carbon Ω‐3 equivalent of arachidonic acid, together with competitive inhibition of arachidonic acid metabolism by both EPA and the 22‐carbon Ω‐3 fatty acid docosahexaenoic acid (DHA) 25,26,31 .…”
Section: Antihypertensive Effects Of ω‐3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%